Practical clinical oncology - Hanna, Louise; Crosby, Tom; Macbeth, Fergus (Cambridge : Cambridge University Press, 2015)
Practical Clinical Oncology, 2nd edition, provides a practical and comprehensive review of the current management of common types of cancer. Introductory chapters give background information on the main treatment modalities and other key issues such as acute oncology, palliative care and clinical research, with new chapters on pathology and advanced external beam radiotherapy. Subsequent chapters describe the diagnosis and treatment of malignancies, based on tumour site or type. Finally, multiple choice questions allow the reader to test their knowledge. This edition has been fully updated to reflect the most current developments in radiotherapy, tumour biology and drug therapy. With an emphasis on practical aspects of cancer care that will be relevant to day-to-day decision making, this book is an invaluable resource on contemporary clinical management of the cancer patient for all trainees and practitioners involved in clinical oncology, medical oncology and palliative care, as well as for specialist nurses and radiographers.
1. Practical issues in the use of chemotherapy in cancer -- 2. Biological treatments in cancer -- 3. Hormones in cancer -- 4. Pathology in cancer -- 5. Radiotherapy planning 1: fundamentals of external beam and brachytherapy -- 6. Radiotherapy planning 2: advanced external beam radiotherapy techniques -- 7. Research in cancer -- 8. Acute oncology 1: oncological emergencies -- 9. Acute oncology 2: cancer of unknown primary -- 10. Palliative care -- 11. Management of cancer of the head and neck -- 12. Management of cancer of the oesophagus -- 13. Management of cancer of the stomach -- 14. Management of cancer of the liver, gallbladder and biliary tract -- 15. Management of cancer of the exocrine pancreas -- 16. Management of cancer of the colon and rectum -- 17. Management of cancer of the anus -- 18. Management of gastrointestinal stromal tumours -- 19. Management of cancer of the breast -- 20. Management of cancer of the kidney -- 21. Management of cancer of the bladder -- 22. Management of cancer of the prostate -- 23. Management of cancer of the testis -- 24. Management of cancer of the penis -- 25. Management of cancer of the ovary -- 26. Management of cancer of the body of the uterus -- 27. Management of cancer of the cervix -- 28. Management of cancer of the vagina -- 29. Management of cancer of the vulva -- 30. Management of gestational trophoblast tumours -- 31. Management of cancer of the lung -- 32. Management of mesothelioma -- 33. Management of soft tissue and bone tumours in adults -- 34. Management of the lymphomas and myeloma -- 35. Management of cancers of the central nervous system -- 36. Management of skin cancer other than melanoma -- 37. Management of melanoma -- 38. Management of cancer of the thyroid -- 39. Management of neuroendocrine tumours -- 40. Management of cancer in children.
Title from publisher's bibliographic system (viewed on 01 Feb 2016).
Keywords: Oncology; Cancer